Private decentralized cooperation from the action of NGOs in Costa Rica: The case of Costa Rica por Siempre Association - Burgos-Rodríguez, Floricel (2023)
The following paper seeks to address the management of decentralized public and private cooperation of the Costa Rica Por Siempre Association to support Costa Rica’s environmental agenda. With the theory of governance and the sustainable development approach, it is interpreted how other actors carry out decision-making, are assigned resources, take control and coordinate projects, giving greater interaction between the central government and the new actors, generating more networks of public and private cooperation. This study is based on qualitative research that uses interviews with key actors as the main source of research and the review of bibliographic material regarding to decentralized cooperation and NGO issues. The Costa Rica por Siempre Association is analyzed as case study, which is a non-governmental organization established in Costa Rica in 2010 and and is recognized for being one of the few organizations managing a Debt-for-Nature Exchange trust with the USA. The case study allows us to identify that the execution of the Costa Rican state is sometimes limited in environmental actions and transfers the responsibility of functions to private associations that respond in an effective way to the excecution of plans.